Challenges in Implementing the Merdeka Curriculum by Biology Teachers at SMAN 1 Kolaka - Irawan, Anry (Universitas Sembilanbelas November Kolaka, 2025)
The implementation of the Merdeka Curriculum requires biology teachers to adapt to more flexible, student-centered, and competency-based learning approaches; however, in practice, they still face various challenges at the school level, including at SMAN 1 Kolaka. This study aims to explore the implementation of the Merdeka Curriculum by a Biology teacher at SMAN 1 Kolaka and to identify various challenges encountered during the learning process. A descriptive qualitative approach was employed, with data collected through structured interviews conducted with a Biology teacher of Grade X. The data were analyzed using thematic analysis, which included transcription, coding, and interpretation. The findings indicate that the Merdeka Curriculum has been implemented and is considered more efficient, fostering a more meaningful and enjoyable learning experience for students. However, the teacher still faces difficulties in delivering material to students with diverse cognitive abilities. The study concludes that enhancing teacher competence in designing adaptive lesson plans (RPP) and utilizing technology are crucial strategies to overcome instructional challenges and optimize the implementation of the Merdeka Curriculum. Keywords: Merdeka Curriculum, Biology Teacher, Curriculum Implementation, Lesson Plan (RPP).